2001
DOI: 10.1177/000169930104400401
|View full text |Cite
|
Sign up to set email alerts
|

Welfare States, Solidarity and Justice Principles: Does the Type Really Matter?

Abstract: In this article, we investigate whether and, if so, to what extent, people's notions of solidarity and their choices of justice principles are related to the type of welfare state regime they live under, as well as to individual socio-demographic and ideological factors. We analyse data from the International Social Survey Program 1996 and the European Values Study 1999, which together cover preferences of citizens from 20 welfare states. Hypotheses pertaining to people's notions of solidarity and preferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
282
2
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(301 citation statements)
references
References 30 publications
10
282
2
7
Order By: Relevance
“…Whereas authors using the wide conception link solidarity with the creation of 'programmes that break down class divisions or regional disparities' and argue that the 'maximum scope' of this kind of solidarity is universalism (Cox, 2004: 209), narrow conceptions of solidarity 'focus on the degree to which programs achieve redistributive ends, because redistribution demonstrates a commitment to the least well-off in a society' (Cox, 2004: 209-10). From Goodin et al (1999: 37-55), we can conclude that the diversity in the way the concept is used in the literature may also result from the existence of different types of welfare state regimes (liberal, social democratic, corporatist welfare regime), which go hand in hand with distinctive sets of fundamental values, benefit structures and welfare outcomes (about which, see also Arts and Gelissen, 2001). Besides diversity in the way the concept is defined, much of the literature connects the attainment of solidarity mainly with the provision of public welfare schemes, ignoring and undervaluing the importance of other collectivities such as the family (about which, see Ostner, 2004) and collective agreements as source of solidarity.…”
Section: Solidarity and Solidaristic Effects Of Collective Agreementsmentioning
confidence: 99%
“…Whereas authors using the wide conception link solidarity with the creation of 'programmes that break down class divisions or regional disparities' and argue that the 'maximum scope' of this kind of solidarity is universalism (Cox, 2004: 209), narrow conceptions of solidarity 'focus on the degree to which programs achieve redistributive ends, because redistribution demonstrates a commitment to the least well-off in a society' (Cox, 2004: 209-10). From Goodin et al (1999: 37-55), we can conclude that the diversity in the way the concept is used in the literature may also result from the existence of different types of welfare state regimes (liberal, social democratic, corporatist welfare regime), which go hand in hand with distinctive sets of fundamental values, benefit structures and welfare outcomes (about which, see also Arts and Gelissen, 2001). Besides diversity in the way the concept is defined, much of the literature connects the attainment of solidarity mainly with the provision of public welfare schemes, ignoring and undervaluing the importance of other collectivities such as the family (about which, see Ostner, 2004) and collective agreements as source of solidarity.…”
Section: Solidarity and Solidaristic Effects Of Collective Agreementsmentioning
confidence: 99%
“…But even a reduced risk is still a risk. One would still expect incumbent vote losses after social policy cuts, since we have strong evidence that a large share of citizens strongly support the welfare state (Arts and Gelissen 2001;Gelissen 2000;Roller 1995;Svallfors 1997 Under what conditions, then, has retrenchment of entitlements led to the electoral punishment of governing parties, and when did voters support parties that cut citizens' transfer income? We show that in addition to the unavailability of the stretching opportunity, a crucial precondition for punishment was the elevation of this issue to the top of the electoral campaign agenda by a combination of opposition parties, interest groups, and the mass media.…”
mentioning
confidence: 96%
“…Many authors explain support for redistribution by means of the so-called 'self-interest'-thesis: people prefer the amount of redistribution that benefits them most (Meltzer and Richard, 1981;Arts and Gelissen, 2001;Blekesaune and Quadagno, 2003). Besides respondents' income or their position in the income distribution, self-interested support for redistribution is also spurred on by perceived risk or vulnerability, for instance when people are unemployed or in a flexible labour market position, or when unemployment or labour market flexibility is high in their society (Blekesaune and Quadagno, 2003;Burgoon and Dekker, 2010).…”
Section: A U T H O R C O P Ymentioning
confidence: 99%
“…Country-level characteristics hence have a formative effect on citizens' preferences and behaviour (Arts and Gelissen, 2001;Dallinger, 2010), although it is impossible to determine whether this process is mainly bottom-up (people to government) or top-down (government to people) -causality probably runs both ways. Earlier research on support for redistribution has shown that welfare attitudes are influenced by macro-level characteristics such as economic affluence, political-institutional differences and the level and structure of inequality (Finseraas, 2009;Dallinger, 2010).…”
Section: Housing Regimes: How Contexts Influence Support For Redistrimentioning
confidence: 99%
See 1 more Smart Citation